Phenotypic and Molecular Characterization of Antimicrobial Resistance in Klebsiella spp. Isolates from Companion Animals in Japan: Clonal Dissemination of Multidrug-Resistant Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae - Harada, Kazuki; Shimizu, Takae; Mukai, Yujiro; Kuwajima, Ken; Sato, Tomomi; Usui, Masaru; Tamura, Yutaka; Kimura, Yui; Miyamoto, Tadashi; Tsuyuki, Yuzo; Ohki, Asami; Kataoka, Yasushi (Frontiers in Microbiology, 2016)
The emergence of antimicrobial resistance in Klebsiella spp., including resistance to extended-spectrum cephalosporins (ESC) and fluoroquinolones, is of great concern in both human and veterinary medicine. In this study, we investigated the prevalence of antimicrobial resistance in a total of 103 Klebsiella spp. isolates, consisting of K. pneumoniae complex (KP, n=89) and K. oxytoca (KO, n=14) from clinical specimens of dogs and cats in Japan. Furthermore, we characterized the resistance mechanisms, including extended-spectrum β-lactamase (ESBL), plasmid-mediated AmpC β-lactamase (PABL), and plasmid-mediated quinolone resistance (PMQR); and assessed genetic relatedness of ESC-resistant Klebsiella spp. strains by multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). Antimicrobial susceptibility testing demonstrated that resistance rates to ampicillin, cephalothin, enrofloxacin, ciprofloxacin, trimethoprim/sulfamethoxazole, cefotaxime, gentamicin, tetracycline, chloramphenicol, amoxicillin-clavulanic acid, and cefmetazole were 98.1 %, 37.9 %, 37.9 %, 35.9 %, 35.0 %, 34.0 %, 31.1 %, 30.1 %, 28.2 %, 14.6 %, and 6.8 %, respectively. Phenotypic testing detected ESBLs and/or AmpC β-lactamases in 31 of 89 (34.8 %) KP isolates, but not in KO isolates. Resistances to five of the twelve antimicrobials tested, as well as the three PMQRs (qnrB, qnrS, and aac(6′)-Ib-cr), were detected significantly more frequently in ESBL-producing KP, than in non-ESBL-producing KP and KO. The most frequent ESBL was CTX-M-15 (n=13), followed by CTX-M-14 (n=7), CTX-M-55 (n=6), SHV-2 (n=5), CTX-M-2 (n=2), and CTX-M-3 (n=2). Based on the rpoB phylogeny, all ESBL-producing strains were identified as K. pneumoniae, except for one CTX-M-14-producing strain, which was identified as K. quasipneumoniae. All of AmpC β-lactamase positive isolates (n=6) harbored DHA-1, one of the PABLs. Based on MLST and PFGE analysis, ST15 KP clones producing CTX-M-2, CTX-M-15, CTX-M-55, and/or SHV-2, as well as KP clones of ST1844-CTX-M-55, ST655-CTX-M-14, and ST307-CTX-M-15, were detected in one or several hospitals. Surprisingly, specific clones were detected in different patients at an interval of many months. These results suggest that multidrug-resistant ESBL-producing KP were clonally disseminated among companion animals via not only direct but also indirect transmission. This is the first report on large-scale monitoring of antimicrobial-resistant Klebsiella spp. isolates from companion animals in Japan.